Sistem Otomatisasi Pengangkat Sampah pada Daerah Aliran Sungai Berbasis Internet of Things (IoT) - Winda Agustiarmi Winda; Dr. Resmi Darni, M.Kom Resmi (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2021)
Garbage in the watershed of the city of Padang is the cause of flooding every year. The use of the garbage net method that is stretched horizontally in watersheds has so far been considered ineffective, because waste still accumulates and floats in the watershed so that it still causes flooding, so an automatic garbage lifter is needed from the watershed which is directly connected to the watershed. garbage dump. The method used in this automatic garbage lift system is to use a conveyor, as a tool to raise waste from the watershed to the landfill. While the AT Mega328p Microcontroller is used as the brain of the system which will later function to control the work of DC motors and Servo motors. The Esp8266 module is used as a Wifi module to connect equipment components to the internet network then forwarded to an application that is used to control the on/off switch and as a notifier when river water levels rise/fall with the Internet of Things (IoT) concept. The test results prove that the tool can work well.